Developing Children Character On The Basis Of Islam Nusantara In Prampelan Village Temanggung Central Java - Eny Rahmawati; Husna Nashihin; Fika Khalwa Ngaisyah; Usman Mafrukhin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Various moral cases have occurred, the upheaval associated with the national character’s identity is increasing. This proves as if the eroded character of the nation. This study aims to determinethe formation of children’s character through the Islamic Archipelago tradition in the Prampelan, Kemloko, Temanggung Village. The type of this research is a descriptive study using a qualitative. The study sample was determined using a purposing samping technique, consisting of hamlet head, TPQ ceregivers. and parents representative. Data collection techniques using the model of Miles and Huberman which includes; data reduction, data presentation, and conclusion drawing. Data collection techniques using interview, observation, and documentation. The result of the study are; (1) Islam Nusantara can improve the nation’s character by holding the value of tawasut, tawazun, tasamuh with cultural elements in it. (2) Basides the religious character, Islam Nuantara also improves the nation’s cultural character.